(untitled) (The Pakistan Development Review, 1999)
In a previous study [Ali, Siyal and Sultan (1995)], we observed a big gap between behaviour and desires. Only 35 percent women had the number of children that they had desired. Whereas, a very large number of women had more children than their stated ideal number of children. The same data set also showed that a majority of women (54 percent) either wanted to stop having children or wanted to wait at least two years before having another child [Ali and Rukanuddin (1992)]. In practice, all of these women were not protected; instead only 12 percent were practising contraception [Shah and Ali (1992)]. An argument was put forward that, had these women been empowered to decide about the number of children to be born, the scenario would have been different and small family size norms would have prevailed.